Close observation versus upfront treatment in hepatocellular carcinoma: are the exception points worth the risk?. Issue 1 (11th September 2017) - Tholey, Danielle M; Hornung, Ben; Enestvedt, Charles K; Chen, Yiyi; Naugler, Willscott S; Farsad, Khashayar; Nabavizadeh, Nima; Schlansky, Barry; Ahn, Joseph; Jou, Janice H
Abstract : Introduction: To assess the outcomes of immediate LDT versus observation strategies for T1 hepatocellular carcinoma (HCC) with respect to progression beyond Milan and survival. Method: T1 HCCs were retrospectively reviewed from a multidisciplinary tumour board database between September 2007 and May 2015. In the observation group, T1 lesions were observed until the tumour grew to meet T2 criteria (=2 cm). The treatment group consisted of T1 lesions treated at diagnosis with liver directed therapy (LDT). Kaplan-Meier plots were constructed for tumour progression beyond Milan and overall survival. Results: 87 patients (observation n=56; LDT n=31) were included in the study. A total of 22% (n=19) of patients progressed beyond Milan with no difference in progression between treatment and observation groups (19% vs 23%, p=0.49). Median time to progression beyond Milan was 16 months. Overall transplantation rate was 22% (observation group n=16; treatment group n=3, p=0.04). Median survival was 55 months with LDT versus 36 months in the observation group (p=0.22). In patients who progressed to T2 (n=60), longer time to T2 progression was a predictor of improved survival (HR=0.94, 95% CI 0.88 to 0.99, p=0.03). Conclusions: Immediate LDT of T1 lesions was not associated with increased risk of progression beyond Milan criteria when compared with an observation approach. Longer time to T2 progression was associated with increased survival and may be a surrogate for favourable tumour biology.